Evolution and Dynamics of Islamic Public Finance in Alleviating Extreme Poverty through Green Economic Development in ASEAN Countries: A Bibliometric Analysis (2002–2025) - Syamsu, Nur; Ulum, Wardatul; Jeris; Agustina, Y.A; Haekal, A.; Fatma; Syaifullah (Indonesian Journal of Islamic Economics and Business, 2025)
This study explores the evolution and intellectual landscape of Islamic Public Finance (IPF) research in ASEAN countries from 2002 to 2025, with a particular focus on its role in alleviating extreme poverty and advancing green economic development. Employing a bibliometric approach, it analyzes 229 Scopus-indexed documents using the Biblioshiny application in R Studio to map publication trends, citation networks, conceptual clusters, and patterns of scientific collaboration. The findings indicate a notable thematic shift from traditional zakat and waqf-focused studies toward a more integrated approach linking Islamic social finance with sustainable development goals, particularly SDG 1 (No Poverty) and SDG 13 (Climate Action). Malaysia and Indonesia emerge as central research hubs, bolstered by strong institutional collaborations involving IIUM, Universitas Airlangga, and UIN Jakarta. Keyword co-occurrence and thematic analyses identify sustainable development, Islamic social finance, and poverty alleviation as core research themes, while emerging areas include green fiscal policy and economic empowerment. The study proposes a new conceptual framework—Islamic Public Finance for Sustainable Development (IPF-SD)—which connects fiscal instruments such as zakat, waqf, and sadaqah with digital governance and inclusive growth to promote equitable and environmentally responsible development. This interdisciplinary mapping not only traces the intellectual trajectory of IPF but also underscores its potential as a Shariah-compliant fiscal model for sustainable policy design. The findings offer important implications for policymakers, practitioners, and scholars in incorporating Islamic fiscal instruments into national sustainability strategies and fostering cross-regional collaboration to drive inclusive and green economic transformation.